LIMD1 Increases the Sensitivity of Lung Adenocarcinoma Cells to Cisplatin via the GADD45α/p38 MAPK Signaling Pathway - Zeng, Xiaofei (Front Oncol, 2020)
Objective: To investigate the effect of LIM domain-containing protein 1 (LIMD1) on the sensitivity of lung adenocarcinoma cells to cisplatin and explore the mechanism. Methods: A549 and H1299 cells were transfected with lentivirus to establish LIMD1-overexpressing cell lines and their respective controls. The protein expression of DNA damage-inducible 45 alpha (GADD45α) and p38 mitogen-activated protein kinase (MAPK) was detected by Western blot. The survival of A549-vec, A549-LIMD1, H1299-vec, and H1299-LIMD1 cells after cisplatin treatment was observed by CCK-8, and the viability was calculated accordingly. Then, SB203580 was used to inhibit the activity of the p38 MAPK signaling pathway, after which the survival of A549-vec, A549-LIMD1, H1299-vec, and H1299-LIMD1 cells in response to cisplatin was observed again by CCK-8, and the viability was calculated accordingly. Results: When LIMD1 was overexpressed in A549 and H1299 cells, the levels of GADD45α and p-p38 MAPK were increased, but total p38 MAPK expression showed no significant change. After adding 30 μM cisplatin, the optical density (OD) values of A549-LIMD1 and H1299-LIMD1 cells were significantly lower than those of their respective controls at 24, 48, and 72 h. The viability of A549-LIMD1 and H1299-LIMD1 cells was significantly lower than that of their respective controls at all the times tested (p < 0.05). The Western blot results showed that the expression of apoptotic proteins cleaved caspase 3 and cleaved PARP in cisplatin-treated A549-LIDM1 and H1299-LIMD1 cells was significantly higher than that in their respective control cells. Flow cytometry showed that the apoptosis rates of A549-LIMD1 and H1299-LIMD1 cells were significantly higher than those of their respective controls (p < 0.05). SB203580 significantly inhibited the activation of the p38 MAPK signaling pathway in lung adenocarcinoma cells; however, neither the OD values nor the viability of A549-LIMD1 cells and H1299-LIMD1 cells showed no significant difference from those of their controls at 24, 48, and 72 h after cisplatin and SB203580 treatment (p > 0.05 for both). Western blot analysis showed that after SB203580 was added, the expression of cleaved caspase 3 and cleaved PARP in A549-LIMD1 and H1299-LIMD1 cells presented no significant difference compared with that in their respective controls. Conclusion: LIMD1 increases the sensitivity of lung adenocarcinoma cells to cisplatin by activating the GADD45α/p38 MAPK signaling pathway.